Studi Kelayakan Bisnis Pendirian Bimbingan Belajar Bunda Hajar di Bandung - Nani Juningsih; Patria Supriyoso (Universitas 45 Surabaya, 2024)
With the development of the community's economy and changing patterns of life, especially in urban areas where community mobility is quite high, parents' time in guiding and educating their children in terms of education is of course decreasing. This of course makes English tutoring an alternative choice for parents to prepare and improve their children's ability to speak English. The phenomenon mentioned above indicates that the prospects for establishing English language tutoring services are quite large. English is big business. English language skills are important for one's competitiveness. With good English skills, good competitiveness, which is useful for our country too. However, that doesn't mean we have to forget Indonesian, which has become our national language.With these considerations in mind, the author plans to establish a non-formal educational institution in the form of a business, namely in the form of a service company engaged in the field of English language tutoring (tutoring) institutions with the name